2010
DOI: 10.1007/s12265-010-9252-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Patients Undergoing Postconditioning During ST-Elevation Myocardial Infarction

Abstract: Reperfusion injury may offset the optimal salvage of myocardium achieved during primary coronary angioplasty. Thus, coronary reperfusion must be combined with cardioprotective adjunctive therapies in order to optimize myocardial salvage and minimize infarct size. Forty-three patients with their first ST-elevation myocardial infarction were randomized to myocardial postconditioning or standard of care at the time of primary coronary angioplasty. Postconditioning was performed immediately upon crossing the lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
2
69
0
1
Order By: Relevance
“…[73][74][75][76][77][78][79][81][82][83]86,[91][92][93] In most of the studies, the patient cohorts were small; of note, the 3 studies with the largest patient cohorts were neutral with respect to infarct size. 90,94,96 All studies in adult 97,98 or pediatric [99][100][101][102][103] cardiac surgery reported a significant infarct size reduction, as reflected by biomarker (creatine kinase-muscle brain, and troponin) release.…”
Section: Ischemic Postconditioningmentioning
confidence: 99%
“…[73][74][75][76][77][78][79][81][82][83]86,[91][92][93] In most of the studies, the patient cohorts were small; of note, the 3 studies with the largest patient cohorts were neutral with respect to infarct size. 90,94,96 All studies in adult 97,98 or pediatric [99][100][101][102][103] cardiac surgery reported a significant infarct size reduction, as reflected by biomarker (creatine kinase-muscle brain, and troponin) release.…”
Section: Ischemic Postconditioningmentioning
confidence: 99%
“…Remote preconditioning is unique in that it can be applied during myocardial ischaemia, prior to reperfusion. 42 Garcia et al 46 demonstrated that a simple postconditioning protocol (performed immediately on crossing the lesion with the angioplasty guidewire, and consisting of four cycles of 30 s of occlusion followed by 30 s of reperfusion), applied at the onset of mechanical reperfusion, resulted in a reduction in infarct size, better epicardial and myocardial flow and improved left ventricular function. In addition, the beneficial effects of postconditioning on cardiac function were shown to persist >3 years.…”
Section: Prevention and Treatment Of Ischaemia-reperfusion Injurymentioning
confidence: 99%
“…In addition, the beneficial effects of postconditioning on cardiac function were shown to persist >3 years. 46 …”
Section: Prevention and Treatment Of Ischaemia-reperfusion Injurymentioning
confidence: 99%
“…[58] опубликовали резуль-таты наблюдений за больными ОИМ с подъемом сег-мента ST (n =43). Среднее время от момента возникнове-ния коронарной катастрофы до реперфузии было равно 4,5 ч. Посткондиционирование осуществляли с помощью 4 циклов реперфузии (30 с) и ишемии (30 с).…”
Section: данные клинических наблюденийunclassified